Reinterpretation of the Blackbody Radiation Problem Based on the Unified Complex System Theory - Cui, Weicheng (European Journal of Applied Sciences, 2026)
Taking the Unified Complex Systems Theory (UCST) as the core framework, this paper re-examines the physical essence of blackbody radiation by integrating the historical context of the development of blackbody radiation theory and experimental facts. Through the core perspectives of this theory—including the dualistic ontology, material classification, particle hierarchy division, and the law of dynamic equilibrium—this study systematically analyzes the particle radiation mechanism of blackbody radiation, the root cause of energy discontinuity, and the material basis of electromagnetic waves. It remedies the theoretical contradictions of the "ultraviolet catastrophe" in classical physics and the confusion between matter and energy concepts in quantum theory, providing a new interpretation path for the blackbody radiation problem that is both experimentally supported and logically consistent. Meanwhile, it deepens the application value of the complex systems theory in the field of microphysics.